Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/path.5452
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental control of grade‐specific colorectal cancer morphology by Src regulation of ezrin–centrosome engagement

Abstract: The phenotypic spectrum of colorectal cancer (CRC) is remarkably diverse, with seemingly endless variations in cell shape, mitotic figures and multicellular configurations. Despite this morphological complexity, histological grading of collective phenotype patterns provides robust prognostic stratification in CRC. Although mechanistic understanding is incomplete, previous studies have shown that the cortical protein ezrin controls diversification of cell shape, mitotic figure geometry and multicellular archite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
(126 reference statements)
0
2
0
Order By: Relevance
“…Using tissue clearing of prostate resections, a staging method based on 3D architecture of prostate lesions has demonstrated prognostic value [4]. In CRC, tissue architecture informs on Src activity because Src induces ezrin which changes the morphology of cells and multicellular structures, informing on prognosis [86].…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Using tissue clearing of prostate resections, a staging method based on 3D architecture of prostate lesions has demonstrated prognostic value [4]. In CRC, tissue architecture informs on Src activity because Src induces ezrin which changes the morphology of cells and multicellular structures, informing on prognosis [86].…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Initial studies demonstrated that the critical T567 on C-ERMAD could be phosphorylated by Rho-kinase (ROCK) ( Ding et al, 2022 ), STE20-like protein kinase (SLK) ( Garland et al, 2021 ), lymphocyte-oriented kinase (LOK) ( Senju and Tsai, 2022 ) and protein kinase C(PKC) ( Khan et al, 2022 ) both in the laboratory and in living organisms. Ezrin Y145, Y353 and Y477 can be modified by phosphorylation through the action of Src kinases and the intrinsic Tyr kinase activity of receptors for epidermal growth factor, hepatocyte growth factor and Platelet-derived growth factor ( Huang et al, 2018 ; Derouiche and Geiger, 2019 ; Rainey et al, 2020 ).…”
Section: The Post-translational Modifications Of Ezrinmentioning
confidence: 99%